2006
DOI: 10.1111/j.1440-1746.2006.04818.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors that predict cecal insertion time during sedated colonoscopy: The role of waist circumference

Abstract: Female sex, poor bowel preparation, smaller waist circumference, lower body mass index and older age were associated with a longer insertion time. Waist circumference was a better predictor than body mass index in assessing cecal insertion time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
54
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 15 publications
7
54
1
Order By: Relevance
“…It reduces cecal intubation, 1 leads to missed diagnosis, 2-4 slows intubation 5 and withdrawal, 3 makes electrocautery dangerous, 6 and increases the cost of colonoscopy delivery. 7 In the present study, we investigated whether a patient's description of the color and consistency of the last rectal effluent before colonoscopy could predict the quality of bowel preparation at colonoscopy, and we evaluated other clinical factors as predictors of preparation quality.…”
mentioning
confidence: 99%
“…It reduces cecal intubation, 1 leads to missed diagnosis, 2-4 slows intubation 5 and withdrawal, 3 makes electrocautery dangerous, 6 and increases the cost of colonoscopy delivery. 7 In the present study, we investigated whether a patient's description of the color and consistency of the last rectal effluent before colonoscopy could predict the quality of bowel preparation at colonoscopy, and we evaluated other clinical factors as predictors of preparation quality.…”
mentioning
confidence: 99%
“…Older age was associated with longer CIT, as the elasticity of the colon decreases and loops are formed more easily with increasing age 8. Previous studies also found that patients with lower BMI were more difficult to intubate 8,9. BMI is correlated with visceral fat, and there is more robust colon support when there is more visceral fat, resulting in less loop formation during CS.…”
Section: Discussionmentioning
confidence: 95%
“…If the gastroenterologist was unable to reach the cecum, the time and location of the furthest point reached were recorded. Time was considered relevant because reaching the cecum tends to occur more efficiently and rapidly when there is no stool present (Hsieh, Kuo, Tseng, & Lin, 2008;Zuber-Jerger, Endlicher, & Gelbmann, 2008).…”
Section: Measurement Methods/instrumentsmentioning
confidence: 99%